2020
DOI: 10.1126/sciadv.abd3431
|View full text |Cite|
|
Sign up to set email alerts
|

The gut microbiome defines social group membership in honey bee colonies

Abstract: In the honey bee, genetically related colony members innately develop colony-specific cuticular hydrocarbon profiles, which serve as pheromonal nestmate recognition cues. Yet, despite high intracolony relatedness, the innate development of colony-specific chemical signatures by individual colony members is largely determined by the colony environment, rather than solely relying on genetic variants shared by nestmates. Therefore, it is puzzling how a nongenic factor could drive the innate development of a quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 49 publications
2
60
5
Order By: Relevance
“…Levels of these compounds vary seasonally in the worker’s brains, increasing in summer when foraging activity is the highest, and at different life stages, being lower in brains of newly emerged, germ-free bees [ 94 ]. Furthermore, the gut microbiome plays a key role in the regulation of social behavioral features in honeybees [ 95 ].…”
Section: Honeybee Microbiotamentioning
confidence: 99%
“…Levels of these compounds vary seasonally in the worker’s brains, increasing in summer when foraging activity is the highest, and at different life stages, being lower in brains of newly emerged, germ-free bees [ 94 ]. Furthermore, the gut microbiome plays a key role in the regulation of social behavioral features in honeybees [ 95 ].…”
Section: Honeybee Microbiotamentioning
confidence: 99%
“…Communities of bacterial symbionts play an important role in animal biology, but the factors that shape the composition and acquisition of the microbiome are known for relatively few species. Rapid advancement in microbiome research has demonstrated that bacterial symbionts can influence host nutrition 1 3 , immunity 3 5 , and behavior 6 8 . Thus, understanding the health, physiology, or evolutionary ecology 9 of any given animal species is incomplete without knowledge of their associated microbes.…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of most identified neurotransmitters were regulated by different gut members, corroborating with the roles of gut microbiota in the altered behaviors in the lab and hive experiments. Alternatively, it recently shows that nestmate recognition cues are defined by gut bacteria, possibly by modulating the host metabolism or by the direct generation of the colony-specific blends of cuticular hydrocarbon 67 . In leaf-cutting ants and termites, gut microbiota suppression by antibiotics also influences the recognition behavior toward nestmates, which may be directed by the bacterial metabolites as recognition cues in the feces 68,69 .…”
Section: Discussionmentioning
confidence: 99%